1995
DOI: 10.1212/wnl.45.6.1183
|View full text |Cite
|
Sign up to set email alerts
|

Fluctuations in autonomic nervous activity during sleep displayed by power spectrum analysis of heart rate variability

Abstract: The sympathetic predominance that characterizes wakefulness decreases during non-REM sleep, is minimal in slow-wave sleep, and surges toward mean awake levels during REM sleep. The autonomic balance is shifted toward parasympathetic predominance during slow-wave sleep. This noninvasive method used to outline autonomic activity achieves results that are in complete agreement with those obtained with direct invasive tools.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

27
133
2
2

Year Published

2001
2001
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 253 publications
(164 citation statements)
references
References 0 publications
27
133
2
2
Order By: Relevance
“…54,55 Moreover, there may be more pronounced neurohormonal perturbations and cytokine release during REM sleep caused by apnea and hypopnea, as compared to NREM sleep. [56][57][58][59] All these pathophysiological changes may be the underlying mechanisms to explain why the AHI in REM sleep, but not the AHI in NREM sleep, was significantly associated with cardiovascular remodeling and ventricular diastolic dysfunction in this study. It is also possible that muscular compensatory ability decreases significantly in patient with occult cardiac dysfunction.…”
mentioning
confidence: 60%
“…54,55 Moreover, there may be more pronounced neurohormonal perturbations and cytokine release during REM sleep caused by apnea and hypopnea, as compared to NREM sleep. [56][57][58][59] All these pathophysiological changes may be the underlying mechanisms to explain why the AHI in REM sleep, but not the AHI in NREM sleep, was significantly associated with cardiovascular remodeling and ventricular diastolic dysfunction in this study. It is also possible that muscular compensatory ability decreases significantly in patient with occult cardiac dysfunction.…”
mentioning
confidence: 60%
“…26,27 The autonomic function is even synchronized with REM/non-REM ultradian sleep rhythm. 44 Our daily short-term HRV measurements can partially answer some sleep problems in HD patients.…”
Section: Discussionmentioning
confidence: 99%
“…However, several prior studies have demonstrated that the measurement of HRV while a person is awake may not reflect their HRV state during sleep (13,14), since some delicate alternations -such as sympathetic activation accompanied by hypertension -are not readily detected without conducting a sleep study (13,15). Recent improvements in sleep research techniques (13,(15)(16)(17)(18) now allow us to test whether sleep patterns and sleep-related cardiac autonomic regulation are influenced by long-term night shift work in nurses.…”
mentioning
confidence: 99%